Who buys from farmers' markets and farm shops: The case of Germany - Miroslava Bavorova; İlkay Unay-Gailhard; Mira Lehberger (International Journal of Consumer Studies, 2016)
In this article, we analyze the influence of sociodemographic factors and consumer attitudes toward direct marketing products and sources (outlets) on the frequency of buying food from farmers' markets and farm shops. By conducting an intercept survey with pedestrians in 2011 and 2012, we interviewed a total of n0.167em=0.167em550 consumers. The target regions of the study were the Eastern German federal states. The study uses two ordered logit regression models to investigate consumers' shopping behaviour at farmers' markets and farm shops separately. We find that different factors significantly influence consumers' buying behaviour at the two direct marketing outlets. Specifically, both a more favorable view toward the freshness of directly marketed foods and the intention to support local producers are positively related to consumers' purchase frequency from farmers' markets. In contrast, consumers' purchase frequency from farm shops is significantly influenced by their perception of the cost of the products, confidence in food producers of directly marketed products, perception of the safety of the food and perception of the accessibility of farm shops. The study results indicate that considering consumer behaviour separately for different direct marketing channels for food rather than considering the entire category of local food outlets may provide new and valuable insights.
Keywords: 330; Direct marketing; farmers' markets; farm shops; consumer behaviour; local food; ordered logit regression